Lymphoepithelioma like carcinoma of the urinary bladder, treated with transurethral resection and intravesical Bacillus Calmette Guerin therapy only: A case report: Lymphoepithelioma like carcinoma of the urinary bladder - Okcu, Oguzhan; Hacıhasanoğlu, Ezgi; Koparal, Murat Yavuz (Acta Biomedica Atenei Parmensis, 2021)
Lymphoepithelioma-like urotehelial carcinoma which was first identified by Zukerberg, constitutes 0,4-1,3% of all urothelial carcinomas and has similar histomorphological features with nasopharyngeal lymphoepithelioma.We report a case of predominant lymphoepithelioma like bladder carcinoma in a 72 years old male patient. Transuretheral resection of the bladder and adjuvant intravesical Bacillus Calmette Guerin treatment was applied. The patient is currently at the 16th month after diagnosis and no recurrence or metastasis has been observed in cystoscopic and radiological examinations.